Bewitchment As A Defence In Divorce Cases: An Analysis From Islamic Law Perspective - Mahyuddin, Ismail; Abd Jalil, Borham; Sharifah Intan Safina, Syed Zubir (IACLP, 2014)
There are claims of the use of witchcraft in causing a rift in the relationship of husband and wife. This issue is raised in several marriage and divorce cases in Shari’ah Court in Malaysia, but there is no initiative taken to overcome it. The inexistence of such law makes the processes of consideration and evaluation of the truth of such claims difficult to be conducted. To this day, the issue is left unresolved. This paper aims to evaluate how far the claim that bewitchment can be a defense in divorce cases in Shari’ah Court in Malaysia. By referring to a few relevant cases, this study analyzes the perspective of Islamic law on the divorce cases connected to witchcraft; and how far it can be applied as a defense in a divorce case. The study is very important in helping the judiciary institution to be fair and to fight for the spouse who becomes a victim of witchcraft evilness.